The significance of Immanuel Kant’s philosophy of education towards the philippine education system K-12 education program - Alan A. Bendanillo; Maria Agneta D. Recaldo; Renato B. Caparida, Jr.; Jade Ronan M. Rodriguez; Julie Ann V. Rodriguez; Paul Marie L. Gepitulan; Roberto A. Dinampo (Science and Education, 2023)
Kant stressed on physical education. For Kant, the positive part of physical education is the culture of the school. In school curriculum includes skills training, discretion, and morality which help in the development of the general mental abilities of a child. In this facet, this study has analysed and examined the significance of Immanuel Kant’s philosophy of education so as to gain understanding towards the modern educational system which is the K-12 Program. In the K-12 Program, it has been mandated that all pupils entering Grade 1 should have compulsory undergone kindergarten or pre-school, and the secondary level will add two more years, which is now existing as the senior high school. While considering the fact that significant progress has been made in the Philippine Educational System when the implementation Basic Education Act of 2013 (Republic Act 10533), or most commonly referred to as K-12 Program starting the school year 2012-2013 which is fully implemented in the country, in this paper the researchers argue that there is indeed significance in Immanuel Kant’s educational theory towards the K-12 program in the sphere of Philippine education system.